2021
DOI: 10.1098/rsob.200347
|View full text |Cite
|
Sign up to set email alerts
|

Viral pathogenesis of SARS-CoV-2 infection and male reproductive health

Abstract: Coronavirus disease 2019 (COVID-19) has emerged as a new public health crisis, threatening almost all aspects of human life. Originating in bats, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted to humans through unknown intermediate hosts, where it is primarily known to cause pneumonia-like complications in the respiratory system. Organ-to-organ transmission has not been ruled out, thereby raising the possibility of the impact of SARS-CoV-2 infection on multiple organ systems. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 105 publications
3
12
0
3
Order By: Relevance
“… Beghi et al 2020 25 Italy Narrative Review • COVID-19 is an influenza virus with neurotropic potential, presents with neurological manifestations many individuals • Postinfectious neurological complications are the result of the activation of immune mechanisms and can explain the insurgence of immune-mediated diseases Thomas & Konstantinidis 2021 26 Greece Narrative Review • The pathophysiology of ED remains a labyrinth. • Underlying mechanisms of ED may be vasculogenic, neurogenic, anatomical, hormonal, drug-induced and/or psychogenic • Neurogenic ED consists of a large cohort of ED, accounting for about 10% to 19% of all cases Wu et al 2020 27 China Narrative Review • Viral infections have detrimental impacts on neurological functions, and even to cause severe neurological damage • Coronaviruses (CoV), especially SARS-CoV-2, exhibit neurotropic properties and may cause neurological diseases Roychoudhury et al 2021 28 India Narrative Review • Preliminary findings so far suggest the possibility of both direct and indirect infection ofSARS-CoV-2 in the reproductive system of males and possible impact on general health and well-being potentially leading to infertility • Evidence indicates a possible long-term effect of the pathogenicity of SARS-CoV-2 infection on testicular tissue, which may further impact reproductive performance Lipsky & Hung 2020 3 USA Narrative Review • Plausible theories for why men respond differently to the SARS-CoV-2 infection include sex-related differences in angiotensin-converting enzyme 2 receptors, immune function, hormones, habits, and coinfection rates • Data from the CDC demonstrate disparities among racial and ethnic minorities, with mortality rates for African American and Latino men exceeding those for White or Asian males • Continuing to collect data disaggregated by sex can help us understand why men are more likely to experience severe disease Pennanen-Iire et al 2021 29 Finland Narrative Review • COVID-19 affects sexual function with implications on overall health • Increased awareness of health-...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Beghi et al 2020 25 Italy Narrative Review • COVID-19 is an influenza virus with neurotropic potential, presents with neurological manifestations many individuals • Postinfectious neurological complications are the result of the activation of immune mechanisms and can explain the insurgence of immune-mediated diseases Thomas & Konstantinidis 2021 26 Greece Narrative Review • The pathophysiology of ED remains a labyrinth. • Underlying mechanisms of ED may be vasculogenic, neurogenic, anatomical, hormonal, drug-induced and/or psychogenic • Neurogenic ED consists of a large cohort of ED, accounting for about 10% to 19% of all cases Wu et al 2020 27 China Narrative Review • Viral infections have detrimental impacts on neurological functions, and even to cause severe neurological damage • Coronaviruses (CoV), especially SARS-CoV-2, exhibit neurotropic properties and may cause neurological diseases Roychoudhury et al 2021 28 India Narrative Review • Preliminary findings so far suggest the possibility of both direct and indirect infection ofSARS-CoV-2 in the reproductive system of males and possible impact on general health and well-being potentially leading to infertility • Evidence indicates a possible long-term effect of the pathogenicity of SARS-CoV-2 infection on testicular tissue, which may further impact reproductive performance Lipsky & Hung 2020 3 USA Narrative Review • Plausible theories for why men respond differently to the SARS-CoV-2 infection include sex-related differences in angiotensin-converting enzyme 2 receptors, immune function, hormones, habits, and coinfection rates • Data from the CDC demonstrate disparities among racial and ethnic minorities, with mortality rates for African American and Latino men exceeding those for White or Asian males • Continuing to collect data disaggregated by sex can help us understand why men are more likely to experience severe disease Pennanen-Iire et al 2021 29 Finland Narrative Review • COVID-19 affects sexual function with implications on overall health • Increased awareness of health-...…”
Section: Resultsmentioning
confidence: 99%
“… 17 It has been theorized that that testicular damage may result following COVID-19 infection. 18 , 19 , 28 The ACE2 gene is a receptor of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for COVID-19. High levels of ACE2 expression in testes indicate that SARS-CoV-2 might affect the testes, potentially affecting male sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also documented that men with COVID-19 are more at risk for worse outcomes and death, independent of age [33]. It has been also hypothesized that the male reproductive system could be a potential target of SARS-CoV-2 infection, and could also lead to infertility [34]. To our knowledge, such differences in viral load and infection outcome between male and female minks have not been documented so far.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…1,2 Additionally, the lungs are not unique targets of SARS-CoV -2 and other targets include the heart, liver, kidney and the male reproductive system. [3][4][5][6][7] These studies have suggested that COVID-19 might cause systemic disease.…”
Section: Introductionmentioning
confidence: 99%